Penerapan Model Problem Based Learning (PBL) Untuk Meningkatkan Minat Belajar IPA Siswa Kelas V SDN 34 Baba - Evy Segarawati Ampry (Pinisi Journal Pendidikan Guru Sekolah Dasar, 2024)
This study aims to determine the application of the Problem Based Learning model in increasing interest in learning Natural Sciences for fifth grade students at SDN 34 Baba, Cendana District, Enrekang Regency. This type of research is Classroom Action Research which is carried out in two learning cycles. Each cycle consists of several stages, namely planning, implementation of action, observation and reflection. The subjects in this study were 1 Natural Sciences teacher and 8 fifth grade students at SD Negeri 34 Baba, Enrekang Regency. The main techniques in data collection are carried out by means of observation, questionnaires, and documentation. There are two data analyzes used, namely qualitative and quantitative data analysis, with the stages of calculating student interest questionnaire scores at each meeting and finding the average student interest in learning at the end of the cycle. The results showed that the results of students' interest in learning in cycle I showed class V students who obtained a learning interest score ≥ 25 there were 2 students out of 8 students in class IV and in cycle II showed class V students obtained a learning interest score ≥ 25 there were 7 students from 8 the number of students in class V. In addition, the average interest in learning in class V also increased from the initial condition of 21.5 to 26.9, where from the category of sufficient interest in learning, it became a high category. So it can be concluded that the application of the Problem Based Learning model can increase students' interest in learning science in class V SDN 34 Baba, Cendana District, Enrekang Regency Keywords: Problem-Based Learning, Interest in Learning Science.